Dinamika Pengembangan Ilmu Falak di Pesantren - Fitri Kholilah (LPPM UIN K.H. Abdurrahman Wahid Pekalongan, 2017)
Since the beginning of its development in Indonesia, ilmu falak (astronomy) can not be separated from pondok pesantren (Javanese traditional Islamic boarding school). After studying under their teachers, the scholars then teach the knowledge they obtain through their study to the santri (students at a pondok pesantren). Based on the observation, there are several boarding schools that have developed astronomy, such as Pondok Pesantren Al-Hikmah 2 Brebes Central Java, Pondok Pesantren Salafiyah Kajen Pati Central Java, Pondok Pesantren Tremas Pacitan East Java, Pondok Pesantren Lirboyo Kediri and Pondok Al-Falah Ploso Kediri East Java. This research uses field approach (Field Research) through observation, documentation, and interview. The results of this study indicate that the five pondok pesantren are permanent institutions and quite serious in the development of the science of astronomy, as evidenced by incorporating astronomy into the learning curriculum. In general, the development model of astronomy developed by the boarding schools above is to combine the two theories of calculation, namely classical and contemporary theories.